The Association between Waist-to-Height Ratio and Vascular Characteristics in Normal Body Mass Index - Nurmaulida Hanifah; Nurfitri Bustamam; Hany Yusmaini; Yanti Harjono Hadiwiardjo (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Cardiovascular disease (CVD) is the leading cause of death globally. Male medical students are highly susceptible to CVD risk due to high academic stress and hormonal profiles. Although body mass index (BMI) is commonly used to assess nutritional status, this parameter cannot detect body fat distribution, especially visceral fat, which is more likely to cause CVD than subcutaneous fat. This study aims to investigate the relationship between Waist-to-Height Ratio (WHtR) and vascular characteristics in male medical students with normal BMI. This study used a cross-sectional design and a total sampling technique. Sample characteristics were collected using a questionnaire, while WHtR was measured using a waist circumference tape and a microtoise. Vascular characteristics were measured using an accelerated photoplethysmograph (APG) analyzer, SA-3000P. The participants were 49 male medical students aged 18-22 years, with normal BMI, light or moderate physical activity, and good sleep quality. The results of this study showed that the proportions of suboptimal aging index, arterial elasticity, peripheral elasticity, and wave type level 2 were higher in the high-risk WHtR group than in the normal WHtR group. However, statistical analysis using the Chi-square test indicated that these differences were not statistically significant (p = 0.291; p = 0.742; p = 0.062; p = 0.648, respectively). These findings emphasize the importance of individuals with high-risk WHtR adopting a healthy lifestyle, including regular exercise and a healthy diet, to maintain vascular health.